FAKTOR YANG MEMPENGARUHI PESERTA DIDIK TIDAK DISIPLIN DALAM PROSES BELAJAR DI MTsN KELAS VIII DURIAN TARUNG PADANG - Pernalis, Dapit; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
Ased on observations by the author, it was found that students are not disciplined in the study, then the authors would like to examine the factors that affect student learning in the discipline not MTsN Tarung Durian, with the aim of research is to describe the internal and external factors that affect learners not discipline in learning in MTsN Tarung Durian. This research is a descriptive study. Of researchers took the study population was all students in Tarung Durian in class VIII MTsN the academic year 2011/2012. By sampling random sampling technique. Sample size was 68 people. Data analysis using the percentage formula.Results of research conducted can be described as follows: 1) The internal factors affecting learners do not learn in the discipline in MTsN Durian Tarung included in the category of very many, is visible from, a) physical factors ,b) psychological factors 2) external factors that affect undisciplined learners in learning in MTsN Durian Tarung including on many categories, is visible from, a) family factor, factor b) school factors, c) factors. The suggestion of this research is expected to the school and parents to pay more attention to learners learn to be more disciplined in order to better learning outcomes.